Plasma‐Enabled Graded Nanotube Biosensing Arrays on a Si Nanodevice Platform: Catalyst‐Free Integration and In Situ Detection of Nucleation Events (Adv. Mater. 1/2013). (2nd January 2013) - Kumar, Shailesh; Mehdipour, Hamid; Ostrikov, Kostya (Ken)
<x xml:space="preserve">Abstract</x> Linear arrays of vertically aligned carbon nanotubes (VACNTs) can be produced by directly exposing thin linear features written on a Si wafer to non‐uniform plasmas, as reported by Kostya (Ken) Ostrikov and co‐workers on page 69. This approach can be used to produce virtually any pattern of linear arrays of VACNTs with variable and graded morphology and structure, without any catalyst or complex nanofabrication. The graded nanotube arrays show competitive performance in electron field emission and biosensing nanodevices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>